The Relationship of Work Position with Low Back Pain in Openwork Craftsmen in Mongolato Village - Sulis Pramutia Rivai; Rona Febriyona; Andi Nur Aina Sudirman (Universitas Ibn Khaldun Bogor, 2024)
Work position is a person's body position in doing work, if the work position done by craftsmen is not suitable it can cause complaints such as low back pain. The purpose of this study was to determine the relationship between work position and low back pain in filigree craftsmen in Mongolato Village. This type of research uses quantitative research with a cross-sectional design, a population of 84 respondents in Mongolato Village, a research sample of 45 respondents, which is determined by purposive sampling techniques, the statistical test used is Chi-Square, a research instrument that is a questionnaire. The results showed that the work position of the craftsmen could trigger low back pain and obtained a value of p-value = 0.009<0.05. Based on the resultsof the analysis of 45 respondents, it is known that craftsmen who have low-risk work positions experience low back pain in 6 respondents, where 5 respondents have mild low back pain, and 1 respondent has moderate low back pain. Moderate-risk work positions experienced low back pain in 32 respondents, of which 14 respondents had mild lower back pain, and 18 respondents moderate lower back pain. High-risk work positions experienced low back pain in 7 respondents, of which 6 respondents with moderate low backpain, and 1 respondent with high low back pain. The study concluded that there was a relationship between work position and low back pain in filigree craftsmen. The advice from this study is that filigree craftsmen should pay attention to a good and correct work position by stretching muscles.